Nocardia Brain Abscess In A Patient With Advanced HIV-AIDS: Case Report - Muhammad Usman; Valeed Bin Mansoor; Nasim Akhtar; Muhammad Arqam Miraj (Journal of Rawalpindi Medical College, 2023)
Nocardia is a gram-positive bacterium that causes localised and disseminated infections. A rare case of Nocardia infection in an immunocompromised individual is presented. Nocardiosis should be kept in mind as a diagnosis in immunocompromised patients with a solitary space occupying lesion in the brain.